Creation of a legend: The interinfluence of historiography and romance tradition in the plot about the last Visigothic king Rodrigo - N. K. Kiselyova (Шаги, 2022)
Spanish epic legends, which originated in ancient times in the oral tradition, have come down to us in various written forms — from historiography (prose chronicles) and major epic poems to small folklore lyric-epic genres, such as the Spanish “old” romance (romancero viejo). The question of the genesis, the method of composition and distribution of such plots is one of the most important now. First of all, it’s connected with the problem of stadial or parallel origin of the texts. The article is devoted to the reconstruction of the ancient Spanish plot about Rodrigo, the last king of the Visigoths, in Latin and Old Castilian historiography, including in the “History of Spain” by Alfonso X the Wise. In addition, the reconstructed plot is compared with the folk epic romance about Rodrigo’s last battle with the Moors and the loss of Spain. The cycle of romances formed in the 14th–16th centuries has several separate plots about Rodrigo. The most interesting question here is which of the plots is the principal one in the cycle and goes back to the authentic folk epic text formed in the oral environment. The analysis undertaken in this article allows us to show, on the one hand, how the plot lives and develops in the tradition and what changes it suffers. On the other hand, comparing the reconstructed plot in the chronicle with the text of the romance allows us to try to identify the original text that is the foundation of the cycle and try to prove the parallel development of plots in romances and chronicles.